(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The paper analyses the different legal regime concerning maternity ascer-tainment, as a function of both natural conception and the use of medical technologies, as well as in relation to the genetic ties between the commissioning mother and the child, ties which are absent if the egg has been provided by a donor who is neither the intended mother nor the surrogate. This research points out that the recognition of the intended parent as the legitimate parent can be contested by the son or daughter, based on the biological truth of generation and by means of DNA testing. The best interest of the child, however, is a key argument in favor of the preservation of de facto family ties.